Challenging The Students by Using Video Movie to Improve Students’ Vocabulary on Independent Curriculum - Wijayanti, Rani Amrista; Rahwanda, Delta; Efendi, Yudi; Syaputri, Wuri (ELT-Lectura, 2024)
Based on Independent Curriculum in Indonesia, the goal of teaching learning at junior high school is that the students must be able to develop communicative competence in written as well as in spoken form. The use of video movie was chosen as video is an appropriate media to stimulate and motivate the students’ interest and attention in understanding the unknown words since video makes language more alive and meaningful and helps to bring the real worlds into classroom. This study is Classroom Action Research (CAR) study, means applied 2 cycles. The result shown, cycle 1, there were 18 students (54.54%) who gained score ≥ 55, while in cycle 2 there were 32 students (96 %) who gained score ≥ 60. For the learning process, that is, the students’ activities, there were only 23 students (66%) who did 80% of the activities in cycle 1, but there were 32 students (96%) who did 80% of the activities in cycle 2. Meanwhile, for the teacher’s performance, the teacher got score 62 in cycle 1, then she got 84 in cycle 2 which means that she could teach the students well after implementing the use of video movie.